2013
DOI: 10.1590/s1808-18512013000400008
|View full text |Cite
|
Sign up to set email alerts
|

Is the lasègue sign a predictor of outcome in lumbar disc herniation surgery?

Abstract: Objective: Evaluate the predictive value of the Lasègue sign on self-reported quality of life measures (HRQoL) in patients who undergo microdiscectomy. Methods: 95 patients with clinical and radiological diagnosis of LDH who underwent microdiscectomy were included. The patients were assessed by a neurological examination and answered validated instruments to assess pain, disability, quality of life, and mood disorder in the preoperative period, and 1, 6 and 12 months after surgery. Results: Preoperative Lasègu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In our study, the Lasegue sign was found to be positive in 182 of 345 cases who presented with the complaint of low back pain, and in 162 (89%) of these cases, herniation findings were confirmed by radiology, similar to the rates in the studies mentioned. In addition to these studies, one study reported that only 56.8% (n=54/95) of the patients who underwent microdiscectomy had a positive pre-operative Lasegue sign [17] .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the Lasegue sign was found to be positive in 182 of 345 cases who presented with the complaint of low back pain, and in 162 (89%) of these cases, herniation findings were confirmed by radiology, similar to the rates in the studies mentioned. In addition to these studies, one study reported that only 56.8% (n=54/95) of the patients who underwent microdiscectomy had a positive pre-operative Lasegue sign [17] .…”
Section: Discussionmentioning
confidence: 99%